2020
DOI: 10.1021/acs.organomet.9b00778
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Deoxygenation of Amine and Pyridine N-Oxides Using Rhodium PCcarbeneP Pincer Complexes

Abstract: Rhodium PCcarbeneP pincer complexes 1-L (L = PPh3, PPh2(C6F5), PCy3) readily facilitate deoxygenation of amine and pyridine N-oxides. The resulting complexes exhibit η2-CO coordination of the resulting keto POP pincer ligand. These η2-CO linkages in the metalloepoxide complexes are readily reduced by isopropyl alcohol and various benzylic alcohols. Thus, efficient catalytic deoxygenation of amine and pyridine N-oxides is possible using complexes 1-L and isopropyl alcohol. This represents a pioneering example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
(21 reference statements)
0
22
0
Order By: Relevance
“…Thus far, the cleavage of strong carbon‐element bonds, beyond carbon‐hydrogen bonds, has been little reported using PC carbene P complexes. Of course, strong C−O bonds must be cleaved in the hydrogen or alcohol driven reduction of a metal bound keto‐pincer ligand that forms a necessary step in the catalytic deoxygenation reactions of nitrous oxide or amine/pyridine N ‐oxides (described above) . Similarly, we have described the direct cleavage of keto‐pincer C−O bonds using phosphines as both cooperative ligands and reductants .…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…Thus far, the cleavage of strong carbon‐element bonds, beyond carbon‐hydrogen bonds, has been little reported using PC carbene P complexes. Of course, strong C−O bonds must be cleaved in the hydrogen or alcohol driven reduction of a metal bound keto‐pincer ligand that forms a necessary step in the catalytic deoxygenation reactions of nitrous oxide or amine/pyridine N ‐oxides (described above) . Similarly, we have described the direct cleavage of keto‐pincer C−O bonds using phosphines as both cooperative ligands and reductants .…”
Section: Methodsmentioning
confidence: 88%
“…Piers has demonstrated the step‐wise reactions necessary for the reduction of nitrous oxide to nitrogen and water in the presence of hydrogen, but has so far failed to reconcile these steps into a catalytic cycle . More recently, we reported on the catalytic deoxygenation of amine and pyridine N ‐oxides mediated by a rhodium PC carbene P complex and alcohol reductant …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 We have shown that the rate of addition of N 2 O to the C]Ir bond 40 can therefore be tuned substantially. 44 Furthermore, the rigidication of the ligand tends to favor the PC carbene P form of the ligand vs. the PC sp 3 P form, while also providing greater protection against C-C bond cleavage reactions that destroy the integrity of the ligand in unlinked systems akin to V. 45 The ability of the carbon atom in these PCP pincers to engage in ligand cooperativity has been exploited in hydrogen, 35,46 silane [47][48][49] and other small molecule 40,[50][51][52][53] activations in various systems. Furthermore, in polyhydridic systems, the dibenzylic hydrogen is actively involved in exchange with the metal hydrides, 34,35 increasing the "hydrogen capacity" of these compounds relative to other (for example PNP) polyhydridic pincer complexes and potentially providing new pathways for catalysis.…”
Section: Introductionmentioning
confidence: 99%